Catalisadores de Au suportados aplicados à oxidação preferencial do CO : influência da interação entre Au e Fe nos sítios ativos - Franke, Karen Niége (Universidade Federal de São Carlos, 2017)
New sources of clean energy have been studied, such as hydrogen (H2). Carbon monoxide, a subproduct of its production, poisons the fuel cell. To reach concentrations below 10 ppm, the addition of preferential CO oxidation reaction (PROX-CO) is required. This work is based on the study of behavior of gold and iron catalysts for PROX-CO. Studies point to high activity and good selectivity in PROX-CO with the combination of Au and Fe in catalysts, especially at low temperatures, although there are effects of the iron-gold interaction to be clarified. M. Haruta, H. Kung and I. Green have proposed mechanisms of reaction where the support plays an important role in PROX-CO, either by its O2 vacancies at the interface with the Au NPs or by taking part in the adsorption of CO molecules. Iron oxides become interesting as they are known for their oxygen vacancies and have high oxygen mobility in their network that varies according to the phase of this metal oxide. Results with Au and/or Fe catalysts supported on γ-Al2O3 showed that varying the synthesis, interaction and oxidation state of Au and Fe were modified. Catalysis tests for PROX-CO with previously reduced samples were more active possibly due to the formation of Au+/Au0 ions essentials for the activation and oxidation of CO. AuFeAl sample reduced at 400°C was shown to be most promising for PROX-CO of the samples tested, due both conversion and selectivity. Subsequently, gold catalysts were supported in the phases hematite, goethite and magnetite of iron oxide obtained from different preparation methods with different thermal treatments. These catalysts presented very different performance for PROX-CO. The performance for hematite-supported Au catalysts was higher. The AuHSG catalyst, which at around 110°C, showed a 33% CO conversion with acceptable CO2 selectivity (above 1:1 CO and O2 conversions respectively).
Keywords: Célula combustível; Oxidação preferencial do monóxido de carbono (PROX-CO); Ouro; Ferro; Fases de óxido de ferro; Fuel cell; Preferential oxidation of carbon monoxide (PROX-CO); Gold; Iron; Iron oxide phases; ENGENHARIAS::ENGENHARIA QUIMICA